The magic of the triangle: coexistence, conflict and inclusion. A case study through an intervention program - Miguel Ángel Santos Guerra; Noemí Rodríguez Fernández; Alejandro Rodríguez Martín; María Verdeja Muñiz (Universidad de La Rioja, 2021)
This study is part of the line of work that opts for integrated models of positive coexistence in schools, aimed at promoting participatory systems and acceptance of commitments. The objective was to know how the participants assessed a program to improve coexistence and to value successful educational experiences that set the school as a framework of peaceful and democratic coexistence. The research design is based on case study and was posed with a combination of qualitative (participant observation, in-depth interview, and discussion groups) and quantitative (questionnaire) techniques. The unit of analysis was the coexistence program carried out in a Public School of the municipality of Oviedo. Overall, the climate of coexistence was good. The conflicts raised mainly in the playground, and for the most part was motivated by the relationships formed when playing football. The methodology of the classroom sessions, based on group dynamics, favoured a climate for learning and good relationship between participants. Institutional involvement, and that of the entire educational community, in supporting the program was a key factor in its success.